2016
DOI: 10.1111/hae.13057
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of point‐of‐care ultrasound‐guided intra‐articular corticosteroid joint injections in patients with haemophilic arthropathy

Abstract: Point-of-care ultrasound enabled intra-articular corticosteroid injections that provided highly effective, safe, and relatively long-lasting pain relief in haemophilic arthropathy. This approach should be used to improve pain management in haemophilic arthropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 54 publications
0
30
0
Order By: Relevance
“…In this regard, regular prophylactic therapy should be the most effective treatment for synovial hyperplasia in patients aged ≤10 years, but insufficient for older patients, who may benefit from extra-local therapies, such as radiosynovectomy 19 and intra-articular drug injection. [20][21][22][23][24] Unlike synovial hypertrophy, the osteochondral subscores increased with age in the knee, elbow and overall joints mainly before 30 years of age, then elevated slightly or remained stable. Although not distinct, a similar tendency of ankle osteochondral progression could be concluded.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, regular prophylactic therapy should be the most effective treatment for synovial hyperplasia in patients aged ≤10 years, but insufficient for older patients, who may benefit from extra-local therapies, such as radiosynovectomy 19 and intra-articular drug injection. [20][21][22][23][24] Unlike synovial hypertrophy, the osteochondral subscores increased with age in the knee, elbow and overall joints mainly before 30 years of age, then elevated slightly or remained stable. Although not distinct, a similar tendency of ankle osteochondral progression could be concluded.…”
Section: Discussionmentioning
confidence: 99%
“…tissue and osteochondral alterations in HA [15][16][17][18]. In this regard, regular prophylactic therapy should be the most effective treatment for synovial hyperplasia in patients aged ≤10 years, but insufficient for older patients, who may benefit from extra-local therapies, such as radiosynovectomy19 and intra-articular drug injection [20][21][22][23][24]. Synovial hyperplasia is thought to be a reversible pathological process caused by joint bleeding, 1 but repeated haemarthroses or occult subclinical bleeding tend to cause chronic synovitis, which is harder to eliminate.…”
mentioning
confidence: 99%
“…The duration of pain relief had a median of 8 weeks.The study demonstrated that ultrasound-guided corticosteroid injections for painful haemophilic joints are safe and clinically effective 2. This treatment was prescribed because the lack of sensitivity to substitutive therapy with the deficient coagulation factor during 2 months.…”
mentioning
confidence: 97%
“…These data strengthen the hypothesis that vascular remodelling and angiogenesis contribute significantly to bleed propagation and development of HA, which may partly explain why haemostatic factor replacement alone may not be sufficient [19]. Another application of POC-MSKUS is US-guided joint aspiration and intra-articular corticosteroid injection to alleviate chronic joint pain in PwH with advanced arthropathy as reported by von Drygalski et al, where median pain score decreased from 7 to 1 out of 10 (P < 0.001) with a median duration of pain relief of 8 weeks [20]. More recently, joint lavage followed by injections of triamcinolone and Hylan G-F 20 (viscosupplement) was shown to improve balance, function and bleeding events in severe HA patients [21].…”
mentioning
confidence: 99%